Beyond Cultural Heritage: Local Culture As A Social Mechanism For Interfaith Coexistence In Mataraman Society - Feryani Umi Rosidah; Himmatul Khoiroh; Adinda Maharani; Maula Safira Tohari (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2026)
This research examines the practice of culturally based interfaith coexistence in the Mataraman community in East Java. This study is motivated by the reality of religious diversity in Indonesia, this research focuses on the role of culture in interfaith coexistence in Mataraman, using qualitative methods from sociological and anthropological perspectives. Data collection techniques include interviews, observation, and documentation. Data analysis uses the Miles and Haberman model, namely data reduction, conclusion drawing, and data presentation. The results indicate that the local wisdom of the Mataraman community plays a significant role in building harmonious interfaith coexistence. Cultural values such as cooperation (gotong royong), tepo sliro (community service), and local traditions of village cleanliness, wayang (wayang), jamasan (traditional prayer), and jaranan (traditional Javanese dance) serve as a medium for a